Variation in cultural characteristics, mycelial compatibility and virulence among the isolates of Scierotinia scierotiorum - and S.C. CHATTERJEE, S. AMEER BASHA (Indian Phytopathology, 2007)
Cultural and mycelial compatibility among 20 Indian isolates of Sclerotinia sclerotiorum, collected from different hosts/soil samples from various localities in India, were studied which revealed the variation in colony morphology, mycelial growth rate and sclerotium formation. Out of 20 isolates, 3 did not produce sclerotia. Mycelial incompatibility among the isolates existed. Of 190 combinations tested, only 18 showed compatible reactions leading to identify 13 vegetative incompatibility groups (VIG). Aggressiveness of these isolates was tested on chickpea (Cicer arietinum) and the plant mortality was recorded.